Minimum Wages, Factor Substitution and the Marginal Producer: Comment - Motheral, Cornelia Little (Quarterly Journal of Economics, 1967)
Journal Article Minimum Wages, Factor Substitution and the Marginal Producer: Comment Get access Cornelia Little Motheral Cornelia Little Motheral Board of Governors of the Federal Reserve System Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 81, Issue 2, May 1967, Pages 343–346, https://doi.org/10.2307/1879593 Published: 01 May 1967